Enhancing giant magnetocaloric effect near room temperature by inducing magnetostructural coupling in Cu-doped MnCoGe. (October 2020) - Pal, S.K.; Frommen, C.; Kumar, S.; Hauback, B.C.; Fjellvåg, H.; Helgesen, G.
Abstract: High performance magnetocaloric materials are crucial to realize the energy efficient and environment friendly magnetic cooling/refrigeration technology. We have designed Mn1-x Cux CoGe compounds possessing a giant magnetocaloric effect near room temperature. The magnetic and structural degree of freedom have been coupled by substituting Cu for Mn leading to a first-order magnetostructural phase transformation resulting in a giant magnetocaloric effect over a wide temperature window of 100 K (250–350 K ). A very large entropy change value of 58 J.kg −1 .K −1 corresponding to a magnetic field change of 5 T near room temperature has been obtained for Mn0.89 Cu0.11 CoGe exhibiting a maximum effective refrigerant capacity of 258.2 J.kg −1 . The first-order magnetostructural phase transformation which is essential for the giant magnetocaloric effect has been confirmed by a combinatorial master-curve and Arrott-plot analyses. The results of giant magnetocaloric effect realized in Mn1-x Cux CoGe are comparable to or better than that of the other reported high performing materials, and this material can be of significant importance for the development of environment friendly and energy efficient cooling devices. The approach of magnetostructural coupling by tuning the structural and magnetic transitions for a giant magnetocaloric effect can also be adopted for other materials to design the best solid-state magnetic refrigerant. Graphical abstract: Unlabelled Image Highlights: Enhanced giant magnetocaloric effect is achieved due to an efficient magnetostructural coupling in Mn1-x Cux CoGe compounds. Very large magnetic entropy change of 58 J.kg −1 .K −1 @ μ 0 H = 5 T is obtained near room temperature for Mn0.89 Cu0.11 CoGe. An excellent effective refrigerant capacity of 258.2 J.kg −1 is achieved. Wide temperature window ( 100 K) is obtained for giant magnetocaloric effect in Mn1-x Cux CoGe.